Documentary credit risks and guarantees - مرعي اعتماد; سلمان عثمان (Latakia University Journal - Economic and Legal Sciences Series, 2024)
Documentary credit is considered the most widely used technology in financing foreign trade operations due to its characteristics that guarantee the rights of contracting parties to documentary credits and is a method invented by the international community , to reduce the risk of non- implementation or mis-execution of international sales contracts , These contracts are usually concluded between people who lack trust , where the documentary credit appeared to guarantee both the seller and the buyer what it aims for in terms of protection and to pay the risks that each of them may be exposed to , although documentary credits are considered one of the most important banking operations and play an effective and vital role in the field of foreign trade this does not negate the existence of risks , whether at the level of the issuer the beneficiary , or even the bank , This research came to shed light on the most important risks that the parties to a documentary credit may be exposed to the order to open the credit , the beneficiary , the bank and to explain the guarantees that can limit and reduce these risks